Registration of 'Castella' soft white winter club wheat. Issue 3 (6th August 2021) - Garland Campbell, Kimberly; Allan, Robert E.; Carter, Arron H.; DeMacon, Patricia; Klarquist, Emily; Wen, Nuan; Chen, Xianming; Steber, Camille M.; Morris, Craig; See, Deven; Esser, Aaron; Engle, Doug; et al.
Abstract: Soft white winter club wheat ( Triticum aestivum L. ssp. compactum ) is a specialty class of soft wheat prized for its end‐use quality. Our goal was to develop a broadly adapted club wheat cultivar targeted to the U.S. Pacific Northwest (PNW) with competitive agronomic and end‐use quality characteristics. 'Castella' (Reg no. CV‐1185, PI 695319), a tall semi‐dwarf awnless white‐kernel club wheat, was selected using the bulk‐pedigree breeding method, from the cross NY89‐66‐7131//B980696//'Chukar'. In the seedling stage, Castella is resistant to PSTv‐51 and PSTv‐40 but susceptible to races PSTv‐4, PSTv‐14, and PSTv‐37 of the stripe rust pathogen. Castella exhibited excellent adult‐plant resistance to the pathogen in multiyear trials. Castella is resistant to toxic levels of aluminum and to the biotype of Hessian fly ( Mayetiola destructor Say) that is prevalent in the PNW. Across 72 environments, Castella exhibited competitive grain yields compared with existing club and soft white cultivars and higher grain volume weight than the club wheat check 'Bruehl'. Castella has maintained a falling number above 300 s more frequently than Bruehl and the club wheat 'Pritchett' in multiple testing years. Castella has excellent milling and baking properties including superior sponge cake volume and will increase the quality of the club wheat crop in the PNW. Core Ideas: The soft white club wheat Castella is agronomically competitive. Castella has excellent high‐temperature adult‐plant resistance to stripe rust. Castella has the desired properties for soft club wheat end‐use quality. Castella has multiple disease, pest, and abiotic stress resistance characteristics. Castella maintains a falling number above 300 better than other club cultivars.